Diagnostik und Therapie der Nebenniereninsuffizienz - Harbeck, Birgit; Lehnert, Hendrik (DMW - Deutsche Medizinische Wochenschrift, 2018)
Adrenal insufficiency is a potentially life-threatening endocrine disorder. Therefore, it is very important to detect the symptoms in sufficient time and treat effectively to avoid acute adrenal insufficiency. This article provides an insight into diagnostically procedures and therapeutically specific aspects of this rare endocrine disease.
Keywords: Nebennierenrindeninsuffizienz; Hydrokortison; Stimulationstest; Patientenschulung